Soy isolate protein formula: challenge and benefit to support child’s growth and development - Saptawati Bardosono (World Nutrition Journal, 2020)
The quality of protein and amino acids of soya is being used as soy protein-based formulas in infant feeding to provide nutrition for normal growth and development. There are few indications for their use in place of cow milk-based formula, although it has no advantage over cow milk protein based formula beyond those indications.